Diagnostic System of Children’s Nutritional Status using the Production Rule Method (Journal of Advances in Information Systems and Technology, 2019)
This research develops an expert system to identify the malnutrition problem on the children living in the underdeveloped regions. The purpose of this research is to identify the nutritional status of children in rural areas. The method is used to develop the production rule. The production rule method includes analyzing the needs as a base of the rule development. The stages performed to diagnose the children's nutritional status are the measurement of body weight, height, age, and gender. The results of the research show that the body weight and height do not match the standard deviation (SD) threshold, where the value between <-3SD to <-2SD is categorized as thin. If the value <-3SD it is classified as very thin, while -2 SD up to 2 SD means normal category, and the value > 2 SD is stated as fat. From the mapping of the underdeveloped regions in X village, there are still many malnutrition children with 5% percentage of thin category, and 1% is very thin and suffering from bronchopneumonia.